Degradation of unplasticised poly vinyl chloride based engineering products upon exposure to ultra violet radiation - K. G. Alahapperuma; A. M. P. B. Samarasekara (Tropical Agricultural Research, 2019)
Poly vinyl chloride (PVC) is considered as a widely used polymer for various applications. It is durable, inexpensive and resistant to heat, water and chemicals. Additives such as lubricants, heat stabilizers, plasticizers, impact modifiers, fillers and ultra violet (UV) stabilizers enhance its durability and make it suitable for a range of applications. PVC is used for automobile and other sectors in products ranging from piping and siding, blood bags and tubing, to wire and cable insulation applications. Poly vinyl chloride exhibits high sensitivity to UV rays and it is a life time deciding factor specially in outdoor applications. This study was conducted to analyse the degradation behavior of PVC under the UV environment. Commercially available 32mm PNT7 unplasticised poly vinyl chloride (uPVC) pipes were selected for this research. Initially, tensile strength, elongation, hardness and water absorption properties were analysed. Ultra violet ray exposure test was performed for PVC samples to evaluate the photo-degradation behavior at selected UV exposure time periods. Tensile strength, elongation, hardness, water absorption properties and visual inspection tests were performed after the UV exposure test. Scanning electron microscopic images and differential thermal analysis were also used to analyze the degradation behavior. It was indicated a slight reduction of tensile strength, percentage elongation and hardness of samples with increase of UV exposure time. Scanning electron microscopic images of products showed degraded features after UV exposure test. This study revealed that uPVC based products are resistant to photodegradation by UV rays.